2012
DOI: 10.1002/acr.21688
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with non‐radiographic axial spondylarthritis differ from patients with ankylosing spondylitis?

Abstract: Conclusion.Patients with nr-axSpA were characterized by the low proportion of male patients and the low burden of inflammation compared to patients with AS. While both groups did not differ regarding health status, disease activity, and physical function, they did differ in signs of inflammation; all were higher in patients with AS. Since many patients with nr-axSpA had not developed structural changes after years of symptoms, we propose that those patients should not be regarded as having preradiographic AS b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
199
7
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(253 citation statements)
references
References 26 publications
25
199
7
15
Order By: Relevance
“…Regular exercise is already emphasised as an important aspect of the long-term management of AS [ 1 ] and has been shown to have an analgesic effect [ 65 ] which may help AS patients cope with pain. Masiero et al [ 66 ] found that exercise, in combination with an educational-behavioural program and anti-TNF therapy, had a greater effect on symptoms of disease activity in AS patients than either intervention used alone.…”
Section: Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Regular exercise is already emphasised as an important aspect of the long-term management of AS [ 1 ] and has been shown to have an analgesic effect [ 65 ] which may help AS patients cope with pain. Masiero et al [ 66 ] found that exercise, in combination with an educational-behavioural program and anti-TNF therapy, had a greater effect on symptoms of disease activity in AS patients than either intervention used alone.…”
Section: Exercisementioning
confidence: 99%
“…Patients with ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nraxSpA) share similar burdens of illness in terms of pain, functional impairment, quality of life (QoL) and the need for effective treatment [ 1,2 ]. Pain and stiffness in the axial spine impact functional ability and QoL [ 3,4 ] and patients have associated these symptoms with poor sleep [ 5,6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Описываемые в литературе различия между нр-аксСпА и АС, такие как более высокая активность [9][10][11], худшие функциональные возможности [12] и большая до-ля мужчин среди больных АС [9,10], на основании пред-варительного анализа данных когорты КоРСаР подтвер-дить не удалось, хотя мы ожидали, что наши результаты подтвердят отмеченные выше различия между двумя кли-ническими вариантами аксСпА. И этому есть логичное объяснение.…”
Section: Discussionunclassified
“…По данным U. Kiltz и соавт [12], в группе пациентов с дорентгенологической стадией было больше женщин, а уровень СРБ и функциональная активность значительно выше у пациентов с установленным диагнозом АС, хотя О р и г и н а л ь н ы е и с с л е д о в а н и я Примечание. *-р<0,01.…”
Section: Discussionunclassified